A mathematical model for predicting dates of occurrence of phenologic stages of three soybean cultivars - de Queiroz, Emilson França; Molion, Luiz Carlos Baldicero; Gaudêncio, Celso de Almeida; Garcia, Antônio (Pesquisa Agropecuaria Brasileira, 1996)
This study was carried out in Londrina, PR, Brazil, in order to develop a mathematical model for predicting dates of occurrence of the reproductive stages and the length of the subperiods based on date of emergency or of planting. Soybean cultivars Paraná, Bossier and Santa Rosa, planted in four planting dates - 10/10, 11/10, 12/10 and 01/10 - during the agricultural years of 1976/77 to 1983/84, were studied. A mathematical model was developed for predicting the date of occurrence of the phenological reproductive stages and the length of the subperiods of the cycle. The angular coefficients of the regression equations between date of planting and date of occurrence of the reproductive stage, specially the date of the first reproductive stage (R1), and the maturity date (R8), provided a consistent measure of the sensitivity of the cultivars to the photoperiod. All the coefficients of determination of these equations were highly significant, for all stages. The equations referring the length of the subperiods were also efficient in expressing the sensitivity of the three soybean cultivars studied to photoperiodic variation resulting from plantings at various dates. Angular coefficients for regression equations between date of emergence and total cycle, for cultivars Paraná, Bossier and Santa Rosa, were 0.384, 0.584 and 0.573, respectively.